1988
DOI: 10.1002/dev.420210302
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nonnutritive sucking on heart rate in preterm infants

Abstract: A laboratory and a field experiment used within-subject designs to test the hypothesis that nonnutritive sucking (NNS) reduces heart rate (HR) in preterm infants. Infants in Experiment A were provided a standard pacifier nipple for 30 min under strictly controlled conditions. In the field Experiment B, nursing staff provided infants with a standard pacifier during alternate intervals in a sequence of four interfeed intervals spanning 12 hr. NNS significantly reduced average HR in each experiment. Given the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
2

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 14 publications
0
5
2
Order By: Relevance
“…Previous studies found that when infants suck on a paci®er, fussing and crying is decreased (Field & Goldson, 1984;DiPietro, Cusson, Caughy, & Fox, 1994) as well as HR (Woodson & Hamilton, 1988). In our studies, HR did not decrease with paci®er sucking.…”
Section: Discussioncontrasting
confidence: 67%
“…Previous studies found that when infants suck on a paci®er, fussing and crying is decreased (Field & Goldson, 1984;DiPietro, Cusson, Caughy, & Fox, 1994) as well as HR (Woodson & Hamilton, 1988). In our studies, HR did not decrease with paci®er sucking.…”
Section: Discussioncontrasting
confidence: 67%
“…To our knowledge, this aspect has not been investigated before. Though several reports exist in the literature describing the influence of NNS on HR and peripheral oxygenation [17,[51][52][53] , studied mainly during painful procedures [51] or in gavage-fed preterm infants [17,51,52] , these data are not comparable to ours since these studies were not carried out during sleep and did not differentiate between suckling bursts and rest periods.…”
Section: Discussioncontrasting
confidence: 53%
“…In addition to the soothing and self-calming effects pacifier use has with full-term infants, there are additional benefits for LBW infants. These benefits include energy conservation necessary for oxygenation and growth as indicated by a decreased gastrointestinal transit time (Marchini, Lagercrantz, Feuerberg, Winberg, & Uvnas-Moberg, 1987;Widstrom et al, 1988), possible protection against necrotizing enterocolitis (Pickler & Terrell, 1994), increased weight gain (Measel & Anderson, 1979), earlier oral feedings (Field et al, 1982;Measel & Anderson, 1979), modulation of behavioral state (Gill, Behnke, Colon, McNeely, & Anderson, 1988;Pickler, Higgins, & Crummette, 1993), decreased heart rate (Miller & Anderson, 1993;Woodson & Hamilton, 1988) soothing of Infants interact with their environment in the process of negotiating the developmental process.…”
Section: Background and Significancementioning
confidence: 99%